The Optical Flow Method and Graham’s Algorithm Implementation Features for Searching for the Object Contour in the Mobile Robot’s Workspace (Journal of Universal Science Research, 2024)
This article examines the optical flow method and graham algorithm implementation features for searching for the object contour in the mobile robot’s workspace. The mathematical models of both methods were discussed in detail and then implemented in a Python program using the PyCharm development environment. As part of the study, a number of experiments were carried out, the purpose of which was to evaluate the performance of the optical flow method and the Graham algorithm for extracting the contour of an object. The research results presented in the article highlight the effectiveness of the optical flow method and the Graham algorithm in real-time conditions.